Resource allocation in multi-hop wireless networks - Nitish Ramkumar. (2012)
Wireless mesh networks, though very promising needs to be managed efficiently. By introducing new nodes and gateways, effort needs to be put on maximizing the performance of the network in order to reap the benefits of such networks.